OPTIMAL TRUST BASED ENERGY EFFICIENT PROTOCOL FOR WSN - Yunes Amgahd; Sameer Asayh; Mohamed Alamein (Surman Journal of Science and Technology, 2023)
The, Wireless Sensor Networks (WSNs) have undergone revolutionary development within the realm of communication networks. These networks, comprised of interconnected sensor nodes, collaborate to collect information from their surroundings. Despite the widespread popularity of WSNs, they present various challenges, including transmission issues, reception problems, idle listening, and overhearing problems for traditional sensor nodes. In response to these challenges, numerous researchers have introduced different frameworks to address the limitations of WSNs. A previous system proposed the integration of a Wake-up Radio (WuR) system to mitigate the conventional problems associated with WSNs. While the WuR system demonstrated improved performance, it fell short of industry expectations due to factors such as false wake-up interference, sensitivity range, and frequency allocation, which resulted in increased power consumption and overhead in WSNs. To overcome the limitations of the WuR system, this research introduces a novel framework for WSNs, termed the Optimal Trust-Based Frequency Allocation (OTBFA) framework. The proposed OTBFA operates with low power consumption, mitigates network overhead in WSNs, and optimally allocates resources within the network. The implemented system, using network simulation version 2, exhibits superior performance compared to traditional and previous system networks.